Short Communication: Growth analysis of sentang (Azadirachta excelsa) in agroforestry system - ARIFA MULYESTHI RAHMAWATHI; NURHENI WIJAYANTO; ARUM SEKAR WULANDARI (Society for Indonesian Biodiversity, 2017)
Rahmawathi AM, Wijayanto N, Wulandari AS. 2017. Short Communication: Growth analysis of sentang (Azadirachta excelsa) in agroforestry system. Biodiversitas 18: 589-592. Sentang is one of forestry plants which can be planted in agroforestry system. It is one of the important medicinal plants grown in different agroforestry systems and contains an active compound of azadirachtin. It has cone crown and balance branch that makes it suitable to be cultivated in agroforestry system which utilizes lower stratum or ground. This research aimed to analyze growth and nutrient content of sentang in agroforestry and monoculture system. Plantation site was in Conservation Unit Research Center for Biopharmaceutical IPB. The sentang was two years old. The design was complete randomized design with one factor (cropping system) and two treatments (agroforestry and monoculture). The results showed the increase of sentang height was higher in agroforestry system than the monoculture due to additional nutrition obtained by sentang in agroforestry system derived from fertilizing activity at the beginning of soybean planting. Nutrient content of sentang was higher in agroforestry plot than monoculture. Fertilizing activity of soybean led to an increase of sentang in agroforestry system.